Acoustic analysis of swallowing sounds in tracheostomized patients affected by traumatic brain injury - Lemos,Raquel Guidotti (2020)
ABSTRACT Purpose: to demonstrate the feasibility of using the acoustic analysis of swallowing sounds as a combined method in the clinical assessment of tracheostomized patients affected by traumatic brain injury. Methods: an observational, cross-sectional study. A total of 10 adult patients, in the mean age of 43.6 years, participated. They were hospitalized in wards, semi-intensive, or intensive care units, from May to July 2016. The inclusion criterion involved being affected by traumatic brain injury, confirmed with a CT scan. The Speech Therapy Tracheal Decannulation Protocol was used in the clinical assessment, as well as the cervical auscultation with the Doppler sonar. Fisher’s test was used, resulting in no significant relationship (p > 0.05) between the variables analyzed in the two consistencies and decannulation. Results: the presence of an acoustic signal of laryngeal elevation was observed, as well as noise between the swallowings, and acoustic signal suggestive of residue in 50% of the patients for the consistencies tested. When the peak frequency, mean wave time, presence of residue in between swallowings, and acoustic signal suggestive of residues were correlated with decannulation (Table 5), no significant correlation was verified (p > 0.05) between the variables analyzed in the two consistencies and the decannulation. Conclusion: the study suggests that it is feasible to use the Doppler sonar as a combined method in the clinical assessment of dysphagia for the decannulation of patients affected by traumatic brain injury.